Structural analysis - Yang, Dixiong; Gu, Junfeng; Hu, Xiaofei; Yang, Lei; Chen, Jingjie (EDP Sciences, 2023)
Structural Analysis is a basic course for undergraduate students with majors of civil engineering, engineering mechanics, flight vehicle design, mechanical engineering, naval architecture and ocean engineering etc., and is also an introductory course for undergraduates to learn and master the analysis and design of beam, truss, frame, arch and composite structures for buildings, bridges and flight vehicles and so on. This textbook includes eight chapters, and covers introduction, kinematic analysis of plane member systems, analysis of statically determinate structures, principle of virtual work and deflection calculation, force method, displacement method, influence lines of structures under moving loads, and matrix displacement method. Main features of this textbook lie in: (1) strengthened the interestingness and readability, and increased brief introduction on the developmental history of structural analysis and the important figures; (2) adopted the kinematic method to construct exactly and rapidly the influence lines of forces of statically indeterminate structures proposed by the author, and highlighted the energy principles and methods; (3) increased introducing the backgrounds of engineering applications; (4) from the viewpoints of history, methodology, aesthetic appreciation and creative thinking, inspected structural analysis and strived to cultivate the innovative talents. This book is designed to serve as a textbook for students in fields such as civil engineering, engineering mechanics, flight vehicle design, mechanical engineering, and ocean engineering, as well as a helpful reference for engineers and professionals in related fields.